THE IMPORTANCE OF TEACHERS` LEADERSHIP SKILLS DEVELOPMENT FOR SUCCESSFUL ORGANIZATIONAL CULTURE IN EDUCATIONAL INSTITUTION - Pakalniņa, Rasa; Ročāne, Maija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Discussions of the quality and effectiveness in  education have become topical today. There are different challenges faced by teachers and school leaders at the primary, lower secondary, secondary and upper secondary levels. Therefore, it must be recognised that leadership skills are becoming important for the successful organisation of learning at all stages of education. The relevance of leadership skills is accentuated by the rapidly changing environment of change that also characterises the field of education. In the 21st century, leadership can be associated as a pedagogical and a managerial skill. Leadership skills and openness to change contribute to the growth of an educational institution, and this growth is at the heart of a successful organisational culture. It fosters a genuine concern for the growth of every employee, as well as an institution-driven vision, coherence, ownership, mentoring, accountability and support. These are employees with developed leadership skills who change and transform the system, because no organisation can exist without change. The aim of this publication is to describe and evaluate the impact of leadership skills and openness to change on the development of a successful organizational culture in the educational institution, and to highlight the need for the development of teachers` leadership skills.